EMPIRICAL INSIGHTS INTO THE INFLUENCE OF FINANCIAL DEVELOPMENT ON CAPITAL MARKETS IN SOUTHEAST ASIA - Samosir, Nikolas; Usman, Berto (Fakultas Ekonomi, Universitas Negeri Jakarta, 2024)
The rise of capital markets around the world has paved the way for new research on the relationship between financial development and capital market performance. This becomes relevant as capital markets are now more accessible to foreign capital flows as a result of economic liberalization and globalization. Therefore, this study intends to provide empirical evidence of the impact of financial development proxied by three parts, namely financial access, financial efficiency and financial stability based on critical mass theory. Operationally, this study uses a sample of 6 countries in ASEAN with an annual observation period from 2007 to 2022. With the characteristics and structure of panel data, this study uses panel regression analysis with a total data of 672 observations (country-years). The analysis used also applies a fixed-effects model (FEM) at the country (Country-FE) and year (Year-FE) levels. The results show that there is a positive association between financial access and capital market performance, a negative association between financial efficiency and capital market performance, and a positive association between financial stability and capital market performance.